Teacher Centered Teaching Strategies in Malaysia Rural Primary School - Ghaizi, Zalhisham Abdul; Muhammad, Azhar; Nordin, Mohd Norazmi; Hashim, Siti Noor Aneeis; Akim, Tumisah; Bahadin, Siti Azura; Halim, Ku Hasnan Ku (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to identify teacher -centered teaching strategies for BM primary school teachers in rural areas. Strategies include teacher -centered teaching, student-centered teaching, and material -centered teaching. Strategies focus on teaching techniques and teaching materials. The limitation of this study is only the teacher - centered teaching strategy. The respondents of the study consisted of 100 Malay language subject teachers in rural primary schools, namely 40 male teachers and 60 female teachers. The researcher conducted the study by collecting information based on the questionnaire that was formed. The findings of this study explain that a large number of Malay language teachers have a positive perception of the centralized teaching strategy of Malay language teachers in rural primary schools. They found that teacher-centered teaching strategies have benefits both to teachers, as well as students if used correctly and in accordance with the content of the lesson to be delivered. In relation to the implementation of Malay language teaching with teacher- centered teaching strategy, more than 80% of the teachers involved also gave a positive response. Teachers agree that teacher-centered teaching strategies still need to be applied by Malay language teachers, especially in teaching techniques. The majority of respondents also agreed that teacher -centered, student -centered, and material -centered teaching strategies need to be arranged as well as possible so that teaching outcomes are fully achieved.